Teacher Corrective Feedback in Students’ English Writing at SMAN 3 Selayar - Sakir, Rauf; Sunra, La; Korompot, Chairil Anwar (ARRUS Journal of Social Sciences and Humanities, 2025)
This research aims to explore how teachers deliver corrective feedback on students' English writing in class XI 1 of SMAN 3 Selayar and identify the type of feedback most preferred by students. The findings revealed that English teachers applied three out of six corrective feedback strategies proposed by Rod Ellis, namely Direct Corrective Feedback, Indirect Corrective Feedback, and Metalinguistic Corrective Feedback. Furthermore, data from observation sheets and interviews with several students indicate that Direct Corrective Feedback is the most frequently received and appreciated type of feedback. This is because it enables students to analyze and correct their mistakes effectively while enhancing their understanding of English writing. Additionally, the study suggests that future research employs a longitudinal approach to assess the long-term impact of corrective feedback on students' English writing skills.